Thomas Annan: photographer of Glasgow - Maddox, Amanda 1948-; Stevenson, Sara (The J. Paul Getty Museum, 2017)
"A survey of the life and publication history of the nineteenth-century Scottish photographer Thomas Annan"...Provided by publisher